(untitled) (Bon Voyage, 2023)
This article analyses the themes of love, longing and fear of abandonment felt by the female characters Hisila in Reply from Tibet and unnamed wife of unnamed narrator in Letter From A Lhasa Merchant to His Wife. Torn between love and fear of abandonment/social ostracization or of non-fulfi llment of love, both Hisila and the wife exhibit conflicting feelings of deep love alongside strong indifference or even scorn towards their lover Yami and husband respectively. This article studies these contrasting emotions under the critical framework of psychoanalytic concept of ambivalence which denotes prevalence of two polar emotions or attitudes towards a person, object or situation. The article concludes that Hisila’s rejection of Yami’s marriage proposal alongside urging him to become her brother, and the wife’s converting into nun but saving her husband’s letter until her death testifies the ambivalence in these characters.